2017
DOI: 10.3892/mmr.2017.6384
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects in workers exposed to naturally occurring asbestos fibers

Abstract: Natural asbestiform fibers are defined 'naturally occurring asbestos' (NOA) and refer to the mineral as a natural component of soils or rocks. The release of NOA fibers into the air from rocks or soils by routine human activities or natural weathering processes represents a risk for human beings. Fluoro-edenite (FE) is a NOA fiber detected in the benmoreitic lava in the area of Biancavilla, South-west slope of Mt. Etna. The aim of the present study was to investigate FE immunotoxicity pathways in a group of 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 92 publications
1
22
0
1
Order By: Relevance
“…Epidemiological studies have indeed confirmed that FE fibers have shown similar effects to those already reported after exposure to asbestos fibers ( 8 , 41-43 ) including cell necrosis with release of high mobility group protein B1 and activation of the Nalp3 inflammasone, leading to chronic inflammation, DNA damage and carcinogenesis ( 44 ).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Epidemiological studies have indeed confirmed that FE fibers have shown similar effects to those already reported after exposure to asbestos fibers ( 8 , 41-43 ) including cell necrosis with release of high mobility group protein B1 and activation of the Nalp3 inflammasone, leading to chronic inflammation, DNA damage and carcinogenesis ( 44 ).…”
Section: Introductionsupporting
confidence: 58%
“…Previous cross-sectional studies conducted on subjects exposed to FE fibers confirm the in vitro , in vivo and ex vivo data. In fact, it has been demonstrated that exposure to FE fibers may induce autoimmunity ( 95 , 96 ), and the involvement of the inflammosome ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of MPM cases are associated with exposure to asbestos fibers; however, other asbestos-like fibers have been considered agents to promoting MPM, such as erionite and fluoro-edenite (FE) fibers. [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The latter kind of fiber has raised the attention of the scientific community as a result of an increase in the incidence and mortality of MPM in Biancavilla, a small town on the southwest slope of Mt.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental investigations showed the presence of FE fibers in the lava rocks excavated from a local stone quarry and used locally for about 50 years for house and road construction building purposes. In vitro, in vivo and epidemiological studies have demonstrated that FE fibers share size and morphological similarities with tremolite amphibolic asbestos fibers [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Therefore, FE fibers have been declared carcinogenic to humans by the International Agency for Research on Cancer (IARC; Lyon, France) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the environmental exposure to the Fluoro-edenite mineral fibers, an amphibolic fiber that is found in the Etna volcanic rock, extracted in local quarries and used in construction, has been associated with an increase in MM cases among the population of Biancavilla in Sicily, Italy [ 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Malignant Pleural Mesotheliomamentioning
confidence: 99%